Paternity Leave Policy In The Mother and Child Welfare Act - Nabilah Farah Dibah; M. Rizqi Azmi; Puti Mayang Seruni; Lidia Febrianti; M Rasyid Al-Qarni; Zikri Fahrazi Hasbullah (Sabtida, 2026)
Mothers experience a transition period involving major physical and psychological changes during pregnancy, childbirth, and childcare. During the process of adapting to their new role as mothers, they often experience heightened emotional sensitivity, stress, and even the risk of self-harm. This phenomenon can naturally impact a mother's mental health. In situations like this, the father's participation is very important in helping mothers meet their psychological needs. A mother's mental health will be maintained because the father actively accompanies and is involved in the parenting process, creating an environment where the mother does not feel alone, but is fully supported by her husband. In addition, mothers will also feel a sense of well-being because the parenting process is carried out together, which is manifested through cooperation, mutual respect, effective communication, and a shared sense of responsibility for the parenting process. Father involvement early in a child's life is a major predictor of their involvement later in life; taking paternity leave can lead to greater father involvement during infancy and higher levels of father involvement in adulthood. Thus, the process of developing attachment in children can have long- lasting effects.